Effect of Natural Zeolite-Pozzolan on Compressive Strength of Oil-Polluted Concrete Marine Structures - Hamid Shahrabadi; Sina Sayareh; Hamed Sarkardeh (Salehan Institute of Higher Education, 2016)
Oil pollution into the concrete composed materials, leads to decrease the compressive strength of the constructed structure. In the present study, effect of using a natural pozzolan named Zeolite on concrete structures was tested in different marine conditions. A fixed amount of oil equal to 2% of sand weight was added as the pollution into the concrete composed materials. Natural Zeolite was added into the concrete instead of cement to the mix design with weight percentages of 10, 15 and 20. After preparing and curing, concrete specimens were placed into the three different conditions: fresh water, tidal, and sea water environments. Results of compressive strength tests showed that replacement of natural Zeolite instead of cement significantly increased compressive strength in comparison with control specimens, in all environments. Adding 20% natural Zeolite increased the compressive strength to its highest values about 60-85% higher than control specimens.